2017
DOI: 10.1007/s10029-017-1715-7
|View full text |Cite
|
Sign up to set email alerts
|

Does the laparoscopic treatment of paediatric hydroceles represent a better alternative to the traditional open repair technique? A retrospective study of 1332 surgeries performed at two centres in China

Abstract: PurposeTo evaluate the safety, efficacy and merits of laparoscopic repair in children with hydroceles by comparing the outcomes of laparoscopic repair and the traditional open repair (OR) procedure. The outcomes of the following three laparoscopic percutaneous extra-peritoneal closure (LPEC) approaches were also compared: conventional two-port surgery, transumbilical single-site two-port surgery and single-port surgery.MethodsWe retrospectively compared the demographic, perioperative and follow-up data from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 17 publications
2
26
0
Order By: Relevance
“…The comparison of the length of the operative time for the LA and the OA showed that the duration of the operation was statistically significantly shorter for the LA [ 14 ]. Zhang et al published retrospective study results comparing the two methods of hernia repair in pediatric patients from two medical centers in China and concluded that the LA approach allows completing the surgery faster [ 15 ]. The study results by Bertozzi et al comparing their contemporary experience with the LA to historical controls, when surgery was performed with the OA, suggests that operative time with the LA method is shorter [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of the length of the operative time for the LA and the OA showed that the duration of the operation was statistically significantly shorter for the LA [ 14 ]. Zhang et al published retrospective study results comparing the two methods of hernia repair in pediatric patients from two medical centers in China and concluded that the LA approach allows completing the surgery faster [ 15 ]. The study results by Bertozzi et al comparing their contemporary experience with the LA to historical controls, when surgery was performed with the OA, suggests that operative time with the LA method is shorter [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this development process, if the processus vaginalis is not closed completely and the volume of fluid in the tunica vaginalis cavity is too large, hydrocele can occur. An operation to close the PPV is the preferred treatment (13,14). The traditional OR surgery method first needs to open the inguinal canal and find the PPV for high ligation and turnover of the tunica vaginalis (15).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, with the development of laparoscopic technology, surgeons have also carried out a large number of comparative studies on OR and LR in the treatment of children with hydrocele (22)(23)(24). Zhang et al (13) reported a retrospective study of 1,332 boys with hydrocele in two centers, including 382 cases in the OR group and 950 cases in the LR group. The LR group was divided into three groups: conventional double port, transumbilical single site double port, and transumbilical single port.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A signi cant advantage of laparoscopic ligation is the ability to inspect contralateral defects, which potentially avoids a second operation and additional incision [19][20][21][22] . In pediatric patients, the incidence of recessive hernia is 20.0-43% 23 .…”
Section: Discussionmentioning
confidence: 99%